Impact of Gastrodiplomacy on the Decision Making Process of Sociopreneurs - Anthony Nnamdi Ogbolu (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
Food undeniably is a basic necessity of man, representing our history and culture. Beyond being vital for man’s survival, it is interwoven with political and economic development. In recent times, Food has continued to gain increasing prominence in the international scheme of things giving rise to what is term gastrodiplomacy. This article explores the contemporary field of gastrodiplomacy albeit limited literature, while testing the hypothesis that “There is no impact of perceived importance of gastrodiplomacy on the decision making process of sociopreneurs” at 5% level of significance. Data was collected with the aid of an online questionnaire which was sent to a Social Media group with an estimated number of 25 sociopreneurs from within and outside the ASEAN community. 9 of 10 responses received were completed correctly and used for this study. Results from the analysis revealed that the perceived importance of gastrodiplomacy by sociopreneurs and the influence of gastrodiplomacy on their decision making process are positively correlated and statistically significant. The further implications and contributions of this study are discussed.